Towards A Pax Africana: Southern African development community's architecture and evolving peacekeeping efforts, 1996 - 2009 - Nagar, Dawn Isabel (Department of Political Studies, 2014)
Based on library research this thesis examines the contribution of the SADC's peace and security efforts towards enhancing the larger security on the African continent. While it is acknowledged that peace and security involve peacemaking, peacekeeping and peace building; the research focused only on the peace and security mechanisms of SADC between 1966 and 2009. A central argument is that the SADC's peace and security system does enhance the evolution of a wider AU peace and security architecture. In furtherance of this argument, the thesis addressed the evolution of SADC from its predecessor the SADCC, the evolution of the African Stand by Force and the role of SADC in this process. In the end the study identified the necessity for certain policy reforms to ensure SADC's better contribution to AU's over all peace and security architecture: i) being donor-driven, SADC should remain the driver of its projects and set its own agenda for projects and strengthen its financial management systems in order to attract international funding; ii) SADC members should commit themselves to implementing its policies and strengthening its National Committees (SNCs); iii) The responsibilities of the SADC secretariat need to be revisited to grant it more executive powers on decision-making for achieving its security agenda; iv) Limited and inadequate staffing hampers SADC's overall security objectives, therefore, the SADC secretariat must be supported with additional capacity in competent programme management, planning, monitoring, finance, procurement and administration; and, v) HIV/Aids remains a challenge for SADC's peacekeepers and a policy should be implemented to cater for peacekeepers by specifying a timeframe and length of period for deployment of military personnel on peacekeeping missions with a moratorium set for much high ranking officials overseeing such missions.